2012
DOI: 10.1128/jvi.02018-12
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immunity Restricts Replication of Novel Murine Astroviruses

Abstract: The mechanisms of astrovirus pathogenesis are largely unknown, in part due to a lack of a small-animal model of disease. Using shotgun sequencing and a custom analysis pipeline, we identified two novel astroviruses capable of infecting research mice, murine astrovirus (MuAstV) STL1 and STL2. Subsequent analysis revealed the presence of at least two additional viruses (MuAstV STL3 and STL4), suggestive of a diverse population of murine astroviruses in research mice. Complete genomic characterization and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(110 citation statements)
references
References 63 publications
7
102
0
1
Order By: Relevance
“…Sequence analysis on ϳ500 nucleotides of the ORF2 revealed that our colonies are infected with an MuAstV genotype most similar to STL4 (Fig. 5A) (23). The capsid is 99% similar to STL4 at the nucleotide level and 98% similar via amino acid.…”
Section: Experiments Performed At Least Three Times (A To C) or Twicementioning
confidence: 98%
See 4 more Smart Citations
“…Sequence analysis on ϳ500 nucleotides of the ORF2 revealed that our colonies are infected with an MuAstV genotype most similar to STL4 (Fig. 5A) (23). The capsid is 99% similar to STL4 at the nucleotide level and 98% similar via amino acid.…”
Section: Experiments Performed At Least Three Times (A To C) or Twicementioning
confidence: 98%
“…All of the mice in our IFNaR Ϫ/Ϫ colony are MuAstV positive. This may have occurred through contact with infected animals or bedding, given that cohousing can lead to infection (23), as can exposure to contaminated bedding (B. Sharp et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations